Marriage by Proxy: A Remedy to Divorce and Single Parenting as Presented in Ifá Ogbèdí Divination Poetry - Samuel Kayode Olaleye (Yoruba Studies Review)
Marriage is an important aspect of life in Africa and other nations around the world. In Africa, particularly among the Yorùbá, marriage institution is sacredly ordained by Olódùmarè for the purpose of procreation and mutual help. Therefore, anyone in the society that has attained marriageable age is expected to marry notwithstanding any form of deformity. However, it is unfortunate that the institution of marriage in the world today is facing a lot of hitches leading to divorce, and eventually, single parenting. In the past, marriage by proxy, which means marriage that follows due process with the help of intermediary and Ifá divination, was, considerably helpful in sustaining marital union. However today, some people have attributed the problem of marriage breakup to abandoned culture and modernity through Western education, foreign culture, and religions, while others premise it on women’s liberation. Yet, the latter argument may not be strong enough since many prominent women were successful in their business enterprises and marriage even in times of the gods such as Ajé who had 200 slaves that helped her to take her wares to the market. Whether these shared views are true or there are other factors associated with the issue of marriage and divorce is what this paper tries to find out. Hence, ten men and women were interviewed from each three principal religions in Nigeria and their opinions were content analyzed. Regardless of religious affiliation, at least 82% of the respondents agreed that foreign culture, religion, and education extremely contributed to the decline of African culture, which gave room for divorce of which the end product is single parenting.